2021
DOI: 10.1037/pspa0000261
|View full text |Cite
|
Sign up to set email alerts
|

Does social psychology persist over half a century? A direct replication of Cialdini et al.’s (1975) classic door-in-the-face technique.

Abstract: Many failed replications in social psychology have cast doubt on the validity of the field. Most of these replication attempts have focused on findings published from the 1990s on, ignoring a large body of older literature. As some scholars suggest that social psychological findings and theories are limited to a particular time, place, and population, we sought to test whether a classical social psychological finding that was published nearly half a century ago can be successfully replicated in another country… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…Past research on studying psychological motives behind victim blaming indicated that fundamentalistic religious worldviews (Sheldon & Parent, 2002), a conservatism attitude (Lambert & Raichle, 2000;Williams, 1984), and just world beliefs (e.g., Strömwall et al, 2013;Van den Bos & Maas, 2009) contribute to victim blaming. In Study 3, we replicated these findings-a fact noteworthy in light of the current debate on the crises of confidence in psychological science (e.g., Genschow, Westfal, et al, 2020;Open Science Collaboration, 2015). Moreover, our research extends past findings by demonstrating that belief in free will explains variance in predicting victim blaming in addition to other relevant predictors such as religiosity, political attitudes and just world beliefs.…”
Section: Theoretical Implicationssupporting
confidence: 66%
“…Past research on studying psychological motives behind victim blaming indicated that fundamentalistic religious worldviews (Sheldon & Parent, 2002), a conservatism attitude (Lambert & Raichle, 2000;Williams, 1984), and just world beliefs (e.g., Strömwall et al, 2013;Van den Bos & Maas, 2009) contribute to victim blaming. In Study 3, we replicated these findings-a fact noteworthy in light of the current debate on the crises of confidence in psychological science (e.g., Genschow, Westfal, et al, 2020;Open Science Collaboration, 2015). Moreover, our research extends past findings by demonstrating that belief in free will explains variance in predicting victim blaming in addition to other relevant predictors such as religiosity, political attitudes and just world beliefs.…”
Section: Theoretical Implicationssupporting
confidence: 66%
“…For example, an interesting finding is that anti-free will manipulations appeared to have stronger effects in the US than in Europe. In line with a recent call for crosscultural replications in social psychology (Genschow, Westfal, et al, 2020), future research may explore in more detail the influence of the manipulation on different continents and cultures.…”
Section: How To Move Forward? Possible Steps and Recommendations For Future Researchmentioning
confidence: 90%
“…A contrario, real cases of accidents that have caused brain damage in individuals have stimulated neuropsychological explorations of the functions of different parts of the brain (e.g., Macmillan, 2000), often well before any theory or experimentation in healthy individuals. In social psychology, it is the systematic observation of a sectarian drift that allowed Festinger to create the theory of cognitive dissonance (Festinger, 1956), and that of particularly gifted salesmen allowed Cialdini to initiate the exploration of the principles of social influence, with recent successful replications (Genschow et al, 2021).…”
Section: Rushing To the Experimental Testmentioning
confidence: 99%